The tuber-feeding weevil Listronotus frontalis as a candidate biological control agent for the invasive semi-aquatic plant Sagittaria platyphylla within South Africa - Rogers, Daniel James (Rhodes University, Faculty of Science, Department of Zoology and Entomology)
Sagittaria platyphylla (Engelm.) J.G.Sm. (Alismataceae) is an invasive, aquatic macrophyte originating in the southern United States of America. In South Africa, the plant was first detected in Krantzkloof Nature Reserve, KwaZulu-Natal Province in 2008, and due to its known impact in other countries, it was listed as a Category 1a invader species under the National Environmental Management: Biodiversity Act 2004 (NEM:BA). This invasive plant has proved difficult to manage due to its varied growth forms and reproductive strategies, such as prolific seed and below ground tuber production. Due to the limitations of conventional control mechanisms, biological control is currently being considered as a potential control option. The tuber feeding weevil Listronotus frontalis LeConte (Coleoptera: Curculionidae) has been identified as a candidate biological control agent for this invasive species. The aims of this study were twofold; to firstly determine the importance of tubers to S. platyphylla populations growing in South Africa; and secondly, to determine the biology and suitability of L. frontalis, a tuber feeder, as a candidate biological control agent. Surveys of S. platyphylla populations in South Africa showed that tubers were found in all sampled sites, except for Krantzkloof Nature reserve in KwaZulu-Natal Province. The highest number of tubers was 97.75 Â± 10.62 (SE) m-2 recorded at Jonkershoek in the Western Cape Province. Monthly sampling from two sites in the Eastern Cape Province, the Makana Botanical Gardens and Maden Dam showed that neither season nor water depth affected tuber production. However, the mean number of tubers as well as mass of tubers sampled, were consistently higher (F(1,179) = 20.9542, P < 0.0001) and heavier (F(1, 857) = 585.7293, P < 0.0001) at the Botanical Gardens than at Maden Dam, respectively. The study showed that tubers are an important life stage of S. platyphylla populations and may vary in size and abundance between and within sites. The tuber feeding weevil was shown to develop from egg to ovipositing adult within just over 40 days. Females were recorded to lay up to 48 eggs within a period of one week. Impact studies showed that adult feeding led to a reduction in all but one of the 11 measured plant growth and developmental measurements, including a reduction in the mean mass of the above-ground plant material (F(2,2743) = 12.05, P = 0.002) as well as a reduction in size and abundance of tubers (F(2,58.47) = 9.756, P = 0.0006) and stolons(F(14.943) = 8.7577, P = 0.003). These results are encouraging and suggest that if the insect is released in South Africa, it may prove to be a valuable biocontrol agent. It is concluded that, until suitable biological control options become available in South Africa, the chemical and mechanical control measures currently implemented should continue, however, controlling tubers should be considered during the planning and implementation of these strategies.
Keywords: Listronotus -- South Africa; Arrowhead (Plants) -- South Africa; Arrowhead (Plants) Biological control -- South Africa; Invasive plants Biological control -- South Africa; Insects as biological pest control agents -- South Africa; Plant populations -- South Africa